2021
DOI: 10.3390/ani11051305
|View full text |Cite
|
Sign up to set email alerts
|

Random Forest Modelling of Milk Yield of Dairy Cows under Heat Stress Conditions

Abstract: Precision Livestock Farming (PLF) relies on several technological approaches to acquire, in the most efficient way, precise and real-time data concerning production and welfare of individual animals. In this regard, in the dairy sector, PLF devices are being increasingly adopted, automatic milking systems (AMSs) are becoming increasingly widespread, and monitoring systems for animals and environmental conditions are becoming common tools in herd management. As a consequence, a great amount of daily recorded da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…The other advantages include the reduction of the workload for the staff on the dairy farm, along with the possibility of milking more than twice a day without higher labor costs. However, the AMS does not only include its own robotic milking also represents a completely new management on dairy farms [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other advantages include the reduction of the workload for the staff on the dairy farm, along with the possibility of milking more than twice a day without higher labor costs. However, the AMS does not only include its own robotic milking also represents a completely new management on dairy farms [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This combination is done using the bagging method. Thus, the algorithm is a set of trees each depending on random variables [20]. For the regression cases, RF uses a continuous target variable and, in the classification, there is presence of target variable of categorical type [19].…”
Section: Decision Treementioning
confidence: 99%
“…A number of studies have demonstrated that storing collected data properly in structured databases is a necessary pre-requisite for developing numerical models capable of characterizing the conditions and performance of individual cows [53] as well as to quantify the effects of specific thermo-hygrometric conditions on dairy production [54,55]. The most recent study, which defined, trained, and tested a model developed using machine learning techniques and the Random Forest algorithm to assess a single cow's daily milk production in relation to environmental conditions, achieved excellent results, with an overall average error in predicting total milk production of just 2% [56].…”
Section: Automatic Milking Systemsmentioning
confidence: 99%